Analisis Kinerja Keuangan Bank Syariah Dengan Metode DuPont System Pada PT. Bank BRI Syariah Periode 2016-2019 - Dewi Nurapiah; Moch. Cahyo Sucipto; Eka Ahadiyat Suryana (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2021)
It is very important to measure financial performance by digging up more information contained in financial statements, financial statements are the end result of the accounting process, which must provide useful information for decision making by various parties. This study aims to obtain an overview of the company's financial performance by applying the DuPont System method. In addition, this analysis can evaluate changes in company conditions and performance, whether there is an increase or decrease or both. The variables used in the DuPont System calculation are Return On Investment, Total Asset Turnover, and Net Profit Margin. The method used in this study is quantitative descriptive, the source of the data needed in this study is secondary data, the data used in this study are data published by BRI Syariah Bank and BRI Syariah Bank publication reports that exist at the Service Authority. Finance (OJK). The results of this study indicate that the performance of BRISyariah fluctuates every year. Where tends to decrease at the level of Net Profit Margin, Total Assets Turnover, and Return On Investment. The highest Net Profit Margin for five years occurred in 2016 at 6.16% and the lowest occurred in 2019 at 2.04%. The largest Total Assets Turnover was 0.10 times in 2016 and the lowest was 0.08 times in 2019. The highest Return On Investment was 0.16% in 2016 and the lowest was 0.17% in 2019. This shows that the performance of BRI Syariah Bank in generating profits is said to be poor because it tends to decrease every year, even though the level of the DuPont System at BRI Syariah Banks has fluctuated, but it is still said to be positive due to the determination of the DuPont Syatem level criteria, namely the ROI of BRI Syariah Banks is still quite healthy.